MICROSCALE OXYGEN ISOTOPIC EXCHANGE AND MAGNETITE FORMATION IN THE NINGQIANG ANOMALOUS CARBONACEOUS CHONDRITE - Choi B.G.; Wasson J.T. (My University, 2003)
We report in situ measurements of O-isotopic compositions of magnetite, olivine and pyroxene in chondrules of the Ningqiang anomalous carbonaceous chondrite. The petrographic setting of Ningqiang magnetite is similar to those in oxidized-CV chondrites such as Allende, where magnetite is found together with Ni-rich metal and sulfide in opaque assemblages in chondrules. Both magnetite and silicate oxygen data fall close to the carbonaceous-chondrite-anhydrous-mineral line with relatively large ranges in δ18O in magnetite (-4.9 to +4.2%%) and in silicates (-15.2 to -4.5%%). Magnetite and silicates are not in O-isotopic equilibrium: the weighted average Δ17O (=δ17O - 0.52 x δ18O) values of magnetite are 1.7 to 3.6%% higher than those of the silicates in the same chondrules. The petrological characteristics and O-isotopic disequilibrium between magnetite and silicates suggest the formation of Ningqiang magnetite by the oxidation of preexisting metal grains by an aqueous fluid during parent body alteration. The weighted average Δ17O of -3.3 +/- 0.3%% is the lowest magnetite value measured in unequilibrated chondrites and there is a positive correlation between Δ17O values of magnetite and silicates in each chondrule. These observations indicate that, during aqueous alteration in the Ningqiang parent asteroid, the water/rock ratio was relatively low and O-isotopic exchange between the fluid and chondrule silicates occurred on the scale of individual chondrules.